A STUDY ON QUALITY OF LIFE AMONG ELDERLY IN THE SOUTHERN PART OF THAILAND: A CASE STUDY IN YALA PROVINCE - Mudor, Adhhiyah; Binisris, Aneera; Phatiwikraiwong, Piriya; Prechawuthidech, Panata (PEOPLE: International Journal of Social Sciences, 2017)
There is a rapid increase in the population of the elderly globally, and Thailand was an ageing nation since 2001 Maintaining health, social participation and improving quality of life of the elderly are public health challenges of the 21st. The quality of life among elderly in Yala province is under-researched.This study aims to determine the quality of life and its associated factors among the Elderly in Yala, Thailand. This was a cross sectional study among 330 residents aged 60 years or more in Yala Province in September 2014. Simple random sampling was used to select participants. Study instruments included World Health Organization Quality of Life Questionnaire Brief Version in Thai language WHOQOl_BREF_THAI, Multidimensional Scale for Perceived Social Support, and a questionnaire for Socio demographic variables. Univariate analysis was used to determine associations and P value <0.05 was considered statistically significant. The overall quality of life among the elderly was at the moderate level 2.84 ± 0.64.) The scores of the quality of life of physical and psychological domains were at the moderate level with 2.25 ± 0.52 and 2.44 ± 0.50. Social domain was at the high level with 3.83 ± 0.89. Factors significantly associated with quality of life included gender, marital status, level of education, financial support, co morbidity, eating, speaking and smiling problem.